The impacts of China-Africa economic relation on factor productivity of African countries - Miao Miao; Yushi Jiang; Dinkneh Gebre Borojo (Economies, 2020)
This study attempts to empirically examine the impacts of the China-Africa economic relationship on factor productivity. The two-step system Generalized method of moments (GMM) estimator is applied to analyze the impacts of the Africa-China economic relationship on factor productivity of 44 African countries controlling Africa-China trade, Chinese foreign direct investment (FDI), and aid allocation to African countries for the periods 2003-2017. The estimation strategy controls endogeneity concerns. Another novelty of this study is calculating total factor productivity (TFP) using the regression approach and driving capital stock data. Additionally, the institutional quality index of countries is derived using principal component analysis. The findings of this study refer that the impact of the China-Africa economic relationship on the TFP of African countries is conditional to the domestic institutional quality of African countries. The results imply that the productivity embodied by the Africa-China economic relationship should be backed by the domestic adaptive capacity to use the benefit of China-Africa economic relations to excel factor productivity. Hence, the capability of African countries to benefit from the China-Africa economic relationship to enhance factor productivity should improve the institutional quality.
Keywords: F35; F41; 330; China-Africa; economic relationship; system GMM; TFP